2019
DOI: 10.1111/bph.14785
|View full text |Cite|
|
Sign up to set email alerts
|

What role does the (2R,6R)‐hydronorketamine metabolite play in the antidepressant‐like and abuse‐related effects of (R)‐ketamine?

Abstract: Major depressive disorder (MDD) is a major health concern in which approximately 30% of patients do not response to currently approved antidepressant medications and are classified as treatment-resistant patients. The noncompetitive N-methyl-D-aspartate (NMDA) glutamate receptor antagonist ketamine produces both rapid (<24 hr) and sustained (up to several weeks) antidepressant effects in treatmentresistant patients following acute or repeated i.v. infusions of ketamine (0.5 mg·kg −1 ), a finding that has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, (R)-ketamine seems to be a more potent and longer acting antidepressant compared to (S)-ketamine and (R/S)ketamine (Chang et al, 2019;Hashimoto, 2019;Wei et al 2020). Furthermore, different research groups demonstrated that the active metabolite (2R,6R)-hydroxynorketamine (HNK) of (R)-ketamine might play a role in the potency and the sustained antidepressant-like effects (overview in Hashimoto, 2019 andHillhouse et al, 2019). (R)-Ketamine has approximately three to four-fold lower affinity for blocking the NMDA receptor compared to (S)-ketamine and therapeutically relevant concentrations of (2R,6R)-HNK do not bind to or directly inhibit NMDA receptors (Jelen et al, 2020).…”
Section: Self-administered Psychopathological Outcomesmentioning
confidence: 99%
“…In addition, (R)-ketamine seems to be a more potent and longer acting antidepressant compared to (S)-ketamine and (R/S)ketamine (Chang et al, 2019;Hashimoto, 2019;Wei et al 2020). Furthermore, different research groups demonstrated that the active metabolite (2R,6R)-hydroxynorketamine (HNK) of (R)-ketamine might play a role in the potency and the sustained antidepressant-like effects (overview in Hashimoto, 2019 andHillhouse et al, 2019). (R)-Ketamine has approximately three to four-fold lower affinity for blocking the NMDA receptor compared to (S)-ketamine and therapeutically relevant concentrations of (2R,6R)-HNK do not bind to or directly inhibit NMDA receptors (Jelen et al, 2020).…”
Section: Self-administered Psychopathological Outcomesmentioning
confidence: 99%
“…Lastly, and most importantly, there is a documented history of (2R,6R)-HNK producing null effects (i.e. failing to produce significant effects) in assays used to measure antidepressant effects (See our commentary for more details [31][32][33][34][35].…”
Section: Other Considerationsmentioning
confidence: 99%
“…treatment in stresssusceptible Wistar-Kyoto rats, despite restoring novel object location recognition and Schaffer collateral LTP in vivo. However, the lack of an analysis of the doseresponse relationship (i.e., testing only a single dose) in most of these studies precludes a more informed conclusion on the functional significance of these results, which contrast those from numerous other laboratories [described above; also reviewed in Hillhouse et al (2019)].…”
Section: Behavioral Effectsmentioning
confidence: 99%